2004
DOI: 10.1016/s1047-2797(03)00078-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and mortality: prospective evidence from a population-based study

Abstract: OBJECTIVE-Self-esteem is considered to be importantly associated with both psychosocial states such as depression as well as physical health. There are no population-based studies that examine the association between self-esteem and mortality. The objective of this study was to assess whether low self-esteem was prospectively associated with increased risk of death in a population-based sample of Finnish men.METHODS-A sample of 2682 male residents of Kuopio, Finland were interviewed and followed prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 32 publications
(39 reference statements)
4
37
0
4
Order By: Relevance
“…Higher levels of religiousness (Gillum et al, 2008;Musick et al, 2004), spirituality (Christensen et al, 1994), personal control (Krause & Shaw, 2000), happiness (Chida & Steptoe, 2008;Koopmans et al, 2010;Martin et al, 2002), selfesteem (Stamatakis et al, 2004), and optimism (Giltay et al, 2004;Rasmussen et al, 2009) have all been shown to have protective effects on mortality. Conversely, depression (Almeida et al, 2010;Mykletun et al, 2009;Schoevers et al, 2009) and reports of poorer physical health (Idler & Kasl, 1991;Menec et al, 1999;Phillips et al, 2010) have been identified as posing increased mortality risk.…”
Section: Religious Psychosocial and Health Mechanisms And Longevitymentioning
confidence: 99%
“…Higher levels of religiousness (Gillum et al, 2008;Musick et al, 2004), spirituality (Christensen et al, 1994), personal control (Krause & Shaw, 2000), happiness (Chida & Steptoe, 2008;Koopmans et al, 2010;Martin et al, 2002), selfesteem (Stamatakis et al, 2004), and optimism (Giltay et al, 2004;Rasmussen et al, 2009) have all been shown to have protective effects on mortality. Conversely, depression (Almeida et al, 2010;Mykletun et al, 2009;Schoevers et al, 2009) and reports of poorer physical health (Idler & Kasl, 1991;Menec et al, 1999;Phillips et al, 2010) have been identified as posing increased mortality risk.…”
Section: Religious Psychosocial and Health Mechanisms And Longevitymentioning
confidence: 99%
“…Plusieurs études ont établi, pour les hommes comme pour les femmes âgés, un lien étroit entre comportement de prévention et d'utilisation des services de santé et santé et capacité fonctionnelle (Wolinksky et al, 1995;Carlson, 2001;Stamatakis et al, 2003). Dans cette étude, l'utilisation des services de santé modernes ou traditionnels à titre préventif (pour un bilan de santé) est supposée associée à la santé perçue et à la capacité fonctionnelle.…”
Section: Comportement Préventifunclassified
“…Previous research has explored the effects of some factors associated with depression on physical health outcomes, including childhood abuse [35], a negative attribution style [36], and low self-esteem [37]; however, additional factors associated with depression still remain unexplored. Considering that both Beck's cognitive theory [5] and the hopelessness model [6] propose multiple cognitive vulnerability factors associated with depression (i.e., dysfunctional attitudes, cognitive errors, cognitive triad, negative automatic thoughts, pessimistic cognitive Running head: Depressive Symptoms, Hopelessness, and Cortisol 12 style), studies including multiple psychosocial factors seem fruitful, especially given the interplay that exists between these factors [e.g., 38].…”
Section: Discussionmentioning
confidence: 99%